SPEKTRUM BUNYI ALAT MUSIK KENTONG BERDASARKAN VARIASI JUMLAH LUBANG - Sarah, Siti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
The goal of this research are knowing sound spectrum by kentong; and knowing correlation between the amount of kentong’s hole and sound frequency. The sound is recorded in quite situation with computer which instaled by sound software. Then, the recording sound is analysed the frequency pattern in prominent and harmonic frequency. As a result, the frequency pattern of kentong with one hole formed in prominent frequency. The frequency pattern of kentong with two holes formed in prominent, first harmonic, and second harmonic frequency. The frequency pattern of kentong with three holes formed as same as kentong with two holes. The frequency pattern of kentong with four holes formed until the fiveth harmonic frequency. There is corelation between sound frequency and the amount of kentong with formula y = -86,125x2 + 515,34x + 57,375 dan determinant value = 0,9779.